Role of exidants-antioxidants and radical scavengers in alcohol-induced liver injury in rats - Yıldız ATAMER; Yüksel KOÇYİĞİT; Aytaç ATAMER; Nuriye METE; Naime CANORUÇ; Aydın KETAN (Turkish Journal of Gastroenterology, 2019)
-